Automation of Electricity Management (International Journal of Engineering and Computer Science, 2015)
Nowadays electricity has become the most important aspect of life without which no work can be performed orcompleted. So this paper introduces about electricity management via Android application. As to manage electricity in a veryefficient way, we are providing postpaid and prepaid billing system to customer. Also task of human intervention will getreduced as there will be no manual reading. The meter reading will be transmitted wirelessly to the local server along with themeter number. This data will be fetched by the server and generate bill automatically .The user will be able to view updatedpower consumption as well as billing information in provider web services. When bill is generated SMS alert will be send to theowner's mobile number. If in case the owner has not paid his bill, cut-off warning messages will be send to users via e-mailand SMS